A Multi‐Stimuli‐Responsive Oxazine Molecular Switch: A Strategy for the Design of Electrochromic Materials. Issue 9 (17th April 2018) - Wang, Xiaojun; Gu, Chang; Zheng, Hongzhi; Zhang, Yu‐Mo; Zhang, Sean Xiao‐An
Abstract: A multi‐state and multi‐stimuli‐responsive oxazine molecular switch that combines an electro‐base property and sensitive base/acid‐responsive properties was designed and synthesized. The multi‐state structures of the molecular switch, with different colors, were predicted by comparing the optical properties with reference molecules and confirmed by using NMR spectroscopy. The color‐switching mechanism under stimulation with acids and bases was investigated by using DFT calculations. Three single states can be obtained and the switching is unidirectional under acid and base stimulation. The electrochromic phenomenon of the molecular switch, which combines its electro‐base and base‐sensitive properties, was demonstrated. An electrochromic device that exhibited good electrochromic properties with excellent reversibility (2000 cycles) and high coloration efficiency (804 cm 2 C −1 ) was successfully constructed. Abstract : Multifunctional molecular switches : By endowing an oxazine molecular switch with electro‐base and acid/base‐responsive properties, a new kind of electrochromic material with great performance was successfully fabricated (see figure).